The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1990
DOI: 10.1002/ar.1092270405
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of cancellous bone to overloading in the adult rat: A single photon absorptiometry and histomorphometry study

Abstract: Nine-month-old female rats were subjected to right hindlimb immobilization or served as controls for 0, 2, 10, 18, and 26 weeks and were double-labeled with bone markers. The right limb was immobilized against the abdomen and considered unloaded, while the left limb was overloaded during ambulation. Single-photon absorptiometry was performed on intact femur; static and dynamic histomorphometry were performed on 20 microns thick undecalcified frontal sections of the proximal tibial metaphysis. Changes in the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
1
2

Year Published

1991
1991
2011
2011

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(38 citation statements)
references
References 30 publications
2
33
1
2
Order By: Relevance
“…When the level of load is changed, the model predicted that the architecture adapts by changing the thickness of the struts while maintaining the same number of struts. This is consistent with the results from Jce and Li (26), who found that, in the overloaded limb of a in the bone, by which a local mechanical stimulus can rat, the trabecular number and separation remained affect the local area within a certain distance, is useful unchanged whereas the trabecular thickness increased for the regulation of the maximal local load. If, for instance, we compare the results from the model with the experimental finding that the trabec ular thickness of the iliac cancellous bone in normal significantly.…”
Section: ! ^ésupporting
confidence: 92%
“…When the level of load is changed, the model predicted that the architecture adapts by changing the thickness of the struts while maintaining the same number of struts. This is consistent with the results from Jce and Li (26), who found that, in the overloaded limb of a in the bone, by which a local mechanical stimulus can rat, the trabecular number and separation remained affect the local area within a certain distance, is useful unchanged whereas the trabecular thickness increased for the regulation of the maximal local load. If, for instance, we compare the results from the model with the experimental finding that the trabec ular thickness of the iliac cancellous bone in normal significantly.…”
Section: ! ^ésupporting
confidence: 92%
“…The periosteal mineral apposition rate (MAR) was 76% higher and intracortical MAR was 23% higher in the trained sows. Jee and Li (1990) observed changes in cellular activity of adult rats after 18 and 26 weeks of increased loading. The proximal tibia of loaded animals had overall higher bone density and significantly higher trabecular number, thickness, and density than the tibia in control rats.…”
Section: Mechanical Straw Homeostasismentioning
confidence: 90%
“…Moreover, for all variables, adaptive behavior persisted, despite changes in loading magnitude and direction. Elevated external loads increased Tr.Th, 17,23 and reduced loads caused trabecular thinning and loss of connectivity. 26 Alternative loading directions caused trabeculae to realign accordingly.…”
Section: Discussionmentioning
confidence: 99%